2010
DOI: 10.4067/s0716-97602010000300009
|View full text |Cite
|
Sign up to set email alerts
|

Chagas disease: Present status of pathogenic mechanisms and chemotherapy

Abstract: There are approximately 7.8 million people in Latin America, including Chile, who suffer from Chagas disease and another 28 million who are at risk of contracting it. Chagas is caused by the flagellate protozoan Trypanosoma cruzi. It is a chronic disease, where 20%-30% of infected individuals develop severe cardiopathy, with heart failure and potentially fatal arrhythmias. Currently, Chagas disease treatment is more effective in the acute phase, but does not always produce complete parasite eradication during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 109 publications
(148 reference statements)
2
40
0
8
Order By: Relevance
“…This finding is consistent with the antiparasitic activity of this combination, since it is natural that a reduction in parasitemia and the parasite load is accompanied by a reduction in IFN-␥ levels, as the inflammatory process associated with the infection undergoes resolution (46,47). In contrast, IL-4 levels were higher in all the treatment groups.…”
Section: Discussionsupporting
confidence: 72%
“…This finding is consistent with the antiparasitic activity of this combination, since it is natural that a reduction in parasitemia and the parasite load is accompanied by a reduction in IFN-␥ levels, as the inflammatory process associated with the infection undergoes resolution (46,47). In contrast, IL-4 levels were higher in all the treatment groups.…”
Section: Discussionsupporting
confidence: 72%
“…Since research and development of new specific medicines have been neglected for too many years, Bz remains the reference drug against T. cruzi infection. Strong evidence indicates that during Bz enzymatic processing by the NADPH-cytochrome P-450 system (5,(31)(32)(33), the production of highly reactive electrophilic metabolites overcomes the redox balance of T. cruzi, based on the enzyme dihydrotrypanothione T(SH) 2 , disrupting parasite metabolism and viability (29,33). The role of Sur in T. cruzi metab- Cardiac samples were collected 24 h after the last treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although chemotherapy with Bz is not always successful, no drugs with therapeutic efficiency superior to that of Bz are available (5)(6)(7). Clinical studies have also reported marked side effects of Bz associated with low specificity and systemic toxicity (1,5). These limitations have highlighted the need for more effective and suitable strategies for Chagas disease control (1,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…En la actualidad sólo existen dos fármacos específi cos para el tratamiento de esta enfermedad, los cuales fueron desarrollados hace más de 30 años, uno de ellos es nifurtimox 5 . Este fármaco, un análogo de nitrofuranos, actúa como tripanocida contra todas las formas de T. cruzi 6,7 . El tratamiento de la enfermedad de Chagas se recomienda durante todas sus fases, como también en pacientes con SIDA, trasplante de órganos o que reciben fármacos inmunosupresores, los cuales presentan mayor…”
Section: Introductionunclassified